The Influence Of Viral Marketing And Influencer Marketing On Purchase Decision For Facetology Sunscreen Products With Online Customer Reviews As Mediating Varable - Indrastati, Novia Miki; Roosdhani, Mohamad Rifqy (Jurnal GeoEkonomi, 2026)
This study aims to examine the influence of viral marketing and influencer marketing on the purchase decision of facetology sunscreen, with online customer reviews as a mediating variable. This study uses a quantitative approach, using questionnaires distributed to 150 gen z respondents in jepara who have previously purchased the product. The data was processed using SEM-PLS version 4.0. The results showed that viral marketing had a significant positive impact on purchase decisions, indicating that interesting, informative and entertaining content can drive consumer behavior. Converely, influencer marketing shows a negative and insignificant influence on purchase decisions, indicating that excessive endorsement, lack of authenticity, or a negative public image can reduce consumer trust. Online customer reviews show a significant mediating effect between influencer marketing and purchasing decision, highlighting their role in strengthening consumer credibility and trust. However, online customer reviews do not significantly mediate the relationship between viral marketing and purchasing decision. This study concludes that although viral marketing is effective in driving cunsomer purchasing behavior, the role of influencer marketing is less reliable unless supported by credible online customer reviews. The results of this study provide practical insight for designing digital marketing strategies that utilize viral content and consumer feedback, rather than relying solely on support from influencer marketing.